Household Structure and Contraceptive Use in Nigeria - Opeyemi Fadeyibi; Mayowa Alade; Samuel Adebayo; Temitope Erinfolami; Fatimah Mustapha; Saudatu Yaradua (Frontiers Media S.A., 2022)
BackgroundContraceptive use in Nigeria has been consistently low despite its many benefits and several efforts by government and development partners to increase its uptake. According to the Nigeria Demographic and Health Survey, the use of any modern method staggeringly increased from 4 to 12% over 28 years (1990-2018). Studies have identified factors at the individual, household, and societal levels that affect contraceptive use. While studies have also shown that decisions such as contraceptive behavior and acquisition of family skills may vary according to the individual or societal factors, there is a dearth of knowledge on how household structure and composition influence contraceptive use in Nigeria. This article seeks to contribute to the body of knowledge by exploring contraceptive use within the household context.MethodWe used data from the 2018 Nigeria Demographic and Health Survey to examine the relationship between household structure and contraceptive use. We excluded pregnant and non-married women at the time of the survey from the sample and used multinomial regression analysis to examine the likelihood of using traditional or modern methods of contraception.ResultsResults show that having a large household size, and the presence of multiple wives in the household significantly reduces the likelihood of using any method of contraceptive. The result further shows a significant association between household wealth index and contraceptive use as the use of any method increases with household wealth index, with those from richest households being twice as likely as their counterparts in the poorest households to use traditional methods (OR:2.02, p < 0.05). Also, women living in households headed by older men (25 and above), households with under 5 children, and those living in rural areas have significantly reduced likelihood of using any method.ConclusionThis study highlights the dynamics of contraceptive use among married women considering household composition. While our study serves as a primer to understanding contraceptive use in households where a woman and her spouse are usual household members, improved family planning interventions to increase uptake through demand creation will require deeper and more comprehensive work to understand the dynamics among women in more complex household settings.